«Remov'd from human eyes»: Madness and Poetry 1676-1774 - Natali, Ilaria (Biblioteca di Studi di Filologia Moderna, 2016)
The years 1676 and 1774 marked two turning points in the social and legal treatment of madness in England. In 1676, London's Bethlehem Hospital expanded in grand new premises, and in 1774 the Madhouses Act attempted to limit confinement of the insane. This study explores almost a century of the English history of madness through the texts of five poets who were considered mentally troubled according to contemporary standards: James Carkesse, Anne Finch, William Collins, Christopher Smart and William Cowper were hospitalized, sequestered or exiled from society. Their works cope with representations of insanity, medical definitions or practices, imputed illness, and the judging eye of the 'sane other', shedding new light on the dis/continuities in the notion of madness of this period.